Internos - Sharma, Piyush (2016)
Business plan for Internos. A social networking mobile application that connects people suffering from rare and terminal diseases. Business plan contains the external environmental factors, needs analysis, Marketing and sales strategy and investment proposal along with financial analysis and forecast for 5 years.